2022
DOI: 10.3389/fmed.2022.1051526
|View full text |Cite
|
Sign up to set email alerts
|

Commentary: Maintenance with hypomethylating agents after allogeneic stem cell transplantation in acute myeloid leukemia and myelodysplastic syndrome: A systematic review and meta-analysis

Abstract: Agha I ( ) Commentary: Maintenance with hypomethylating agents after allogeneic stem cell transplantation in acute myeloid leukemia and myelodysplastic syndrome: A systematic review and meta-analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…In the HMA maintenance group, the overall survival and the relapse-free survival were superior; the cumulative incidence of relapse and non-relapse mortality were lower than in the observation group. However, some limitations of this study were reported in a commentary by Beauvais et al ( 9 ), who believed an inaccurate approach to data design and analyses led to an immortal time bias. These authors argued that only a randomized study can demonstrate a definitive conclusion.…”
mentioning
confidence: 82%
“…In the HMA maintenance group, the overall survival and the relapse-free survival were superior; the cumulative incidence of relapse and non-relapse mortality were lower than in the observation group. However, some limitations of this study were reported in a commentary by Beauvais et al ( 9 ), who believed an inaccurate approach to data design and analyses led to an immortal time bias. These authors argued that only a randomized study can demonstrate a definitive conclusion.…”
mentioning
confidence: 82%